Independence, Time Budget Pressure, Audit Fee and Workload on Audit Quality as The Impact of Covid-19 - Munidewi, Ida Ayu Budhananda; Sunarsih, Ni Made; Widyantari, Ida Ayu Made (Journal of International Conference Proceedings, 2020)
This study aims to determine the effect of independence, time budget pressure, audit fees, workload on audit quality as the impact of Covid-19 pandemic on audit firms registered in IAPI Bali. The population of this research are all auditors in 16 audit firms registered in IAPI Bali. This research involved 114 respondents selected by a purposive sampling method with criteria of one-year minimum of service in audit firms. The data were analyzed with multiple linear regression. The results showed that independence has a positive significant effect on audit quality; time budget pressure, audit fees and workloads have no significant effect on audit quality.